Prevalence and treatment of mental disorders in Lebanon - Nasser, Soumana C. (2006)
Background Mental disorders are believed to account for a large portion of disease burden worldwide. However, no national studies have been undertaken to assess this assumption in the Arab world. Methods As part of the WHO World Mental Health (WMH) Survey Initiative, a nationally representative psychiatric epidemiological survey of 2857 adults (aged ⩾18 years) was done in Lebanon between September, 2002, and September, 2003, through a study called LEBANON (Lebanese Evaluation of the Burden of Ailments and Needs Of the Nation). 12-month prevalence and severity of DSM-IV (Diagnostic and Statistical Manual of Mental Disorders, fourth edition) disorders, and treatment were assessed with the WHO Composite International Diagnostic Interview (CIDI, version 3.0). Information was also obtained for sociodemographics and exposure to traumatic events in the Lebanon wars. Findings 308 (17·0%) of respondents met criteria for at least one 12-month DSM-IV/CIDI disorder, 108 (27·0%) of whom were classified serious and an additional 112 (36·0%) moderate. Nearly half of respondents had a history of exposure to war-related traumatic events. Significantly elevated odds ratios (OR) of mood, anxiety, and impulse-control disorders were associated with two (OR 2·0–3·6) or more (2·2–9·1) war-related traumatic events, resulting in substantially higher proportions of moderate and severe 12-month mental disorders in respondents exposed to multiple war-related traumata (16·8–20·4%) compared with other respondents (3·3–3·5%). Only 47 (10·9%) respondents with 12-month disorders obtained treatment. 85% of people were treated in the general medical sector and the mental-health-care system, and the rest by religious or spiritual advisers, counsellors, herbalists, or fortune-tellers. Interpretation Mental disorders are common in Lebanon, with a prevalence equivalent to that in Western Europe. However, the number of individuals with mental disorders who are not receiving treatment is considerably higher in Lebanon than in Western countries.